Case report: Persistent syndrome of inappropriate antidiuresis after traumatic brain injury: spontaneous resolution and impact on RAAS and bone metabolism over five years - Liu, Yaoxia; Tang, Jiao; Zhou, Mingwei; Huang, Haotian; Wang, Tao; Zhang, Min (Frontiers in Endocrinology, 2025)
The syndrome of Inappropriate Antidiuresis (SIAD) is a well-known cause of hyponatremia and can be associated with various etiologies, including traumatic brain injury (TBI). Most cases of SIAD following TBI exhibit a pattern in which hyponatremia develops several days to weeks after the trauma and resolves within a few weeks. Here, we present a rare case of persistent SIAD caused by TBI that resolved spontaneously after five years. The patient experienced prolonged hyponatremia for several years and was ultimately diagnosed with post-traumatic SIAD after excluding other potential causes. Notably, the patient exhibited an unusual sensitivity to tolvaptan, accompanied by decreased renin levels and increased bone turnover markers. The condition resolved spontaneously after five years, with renin, aldosterone, and bone turnover markers returning to normal upon re-evaluation.